Host plant resistance to insects: an ecofriendly approach for pest management and environment conservation - Sharma, H.C.; Ortíz, R. (2002)
Host plant resistance (HPR) to insect is an effective, economical and environment friendly method of pest control. The most attractive feature of HPR is that farmers virtually do not need any skill in application techniques, and there is no cash investment by the resource poor farmers. Considerable progress has been made in identification and development of crop cultivars with resistance to the major pest in different crops